The capture - Lasky, Kathryn (New York : Scholastic, 2010)
Soren, a barn owl that is captured and taken to a special school for orphaned owls, is befriended by elf owl Gylfie and together the two set out to discover what is really going on at St. Aegolius Academy.
"Now the major motion picture Legend of the guardians : the owls of Ga'Hoole"--Cover.
4.8
3-6
3-6
Keywords: Folklore -- Juvenile fiction; Good and evil -- Juvenile fiction; Owls -- Juvenile fiction; Fantasy; Folklore -- Fiction; Good and evil -- Fiction; Owls -- Fiction; Folklore -- Fiction; Good and evil -- Fiction; Movie novels; Owls -- Fiction; Fantastic fiction; Fantastic fiction; Movie novels